Smoking and BDNF Val66Met polymorphism in male schizophrenia: A case-control study. (January 2015) - Zhang, Xiang Yang; Chen, Da-Chun; Tan, Yun-Long; Luo, Xingguang; Zuo, Lingjun; Lv, Meng-Han; Shah, Nurun N.; Zunta-Soares, Giovana B.; Soares, Jair C.
Abstract: Some recent studies show an association between a functional polymorphism of BDNF gene (Val66Met) and the susceptibility to nicotine dependence and we hypothesized that this polymorphism was associated with smoking in both schizophrenia patients and healthy controls. The BDNF Val66Met gene polymorphism was genotyped in 690 chronic male schizophrenia patients (smoker/nonsmoker = 522/169) and 628 male controls (smoker/nonsmoker = 322/306) using a case-control design. Nicotine dependence (ND) was assessed by the cigarettes smoked per day (CPD), the Heaviness of Smoking Index (HSI), and the Fagerstrom Test for ND (FTND). Patients also were rated on the Positive and Negative Syndrome Scale (PANSS). The results showed no significant differences in BDNF Val66Met genotype and allele distributions between the patients and healthy controls or between smokers and nonsmokers in either patients or healthy controls alone. In patient groups, however, the smokers with the Met allele had significantly higher HSI scores (Met/Met: 2.8 ± 1.7 vs. Met/Val: 2.2 ± 1.7 vs. Val/Val: 2.0 ± 1.6, p  < 0.01) and a trend toward a significantly higher FTND score ( p  = 0.09) than those with the Val/Val genotype. In addition, the smokers showed significantly lower PANSS negative symptom and total scores, longer duration of illness and more hospitalizations (all p  < 0.05). In the control group, the smokers with the Met allele started smoking significantly earlier than those with the Val/Val genotype (both p  < 0.05). These results suggest that the BDNF Val66Met polymorphism may affect a smoker's response to nicotine in both schizophrenia and healthy controls from a Chinese Han population, but with differential effects in different aspects of smoking behaviors. Highlights: Putatively, the BDNF Val66Met variant influences the risk for smoking behavior. This variant was genotyped in smokers and nonsmokers in schizophrenia and controls. In patients, the smokers with the Met allele had significantly higher nicotine dependence. In controls, the smokers with the Met allele started smoking earlier.